PENGARUH MEDIA REALIA TERHADAP HASIL BELAJAR IPAS - Anbar Nisrina Huwaida; Ina Magdalena; Yayah Huilatunisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by several factors, namely: the media provided by the school does not meet the needs of students, the surrounding environment is not maximized, and the lack of media use in materials that should involve media. The formulation of the problem proposed in this study is whether realia media has an impact on student IPAS learning outcomes. The purpose of this study was to determine the effect of realia media on the learning outcomes of IPAS on buying and selling material for grade IV students. This research method is a quantitative approach with the type of experimental research, namely research conducted to test the validity of experimental variables. In this study, researchers sampled the entire student population. The data source of this research comes from a sample of 52 students. Based on the results of hypothesis calculation, the value of Thitung (-19.896) < Ttabel (2.009) is obtained. In accordance with the statistical hypothesis that has been made before the research, it can be concluded that there is an effect of realia media on the learning outcomes of IPAS grade IV students at a significance level of 5% (a = 0.05).